Cannabis vaping: Understanding the health risks of a rapidly emerging trend - Chadi, Nicholas (Paediatr Child Health, 2020)
The rapid emergence of youth vaping has completely changed the landscape of adolescent substance use in Canada and has become a pressing public health issue of our time. While nicotine remains the most common substance encountered in vaping devices, cannabis vaping is now reported by one-third of youth who vape. Though cannabis vaping is thought to generate fewer toxic emissions than cannabis smoking, it has been associated with several cases of acute lung injury and often involves high-potency forms of cannabis, exposing youth to several acute and long-term health risks. The low perceived riskiness of cannabis as a substance and of vaping as a mode of consumption may bring a false sense of security and be particularly appealing for youth who may be looking for a ‘healthier way’ to use substances. While research is still lacking on how best to support youth who may have already initiated cannabis vaping, concerted efforts among paediatric providers, public health experts, schools, communities, and families are urgently needed to limit the spread of cannabis vaping among Canadian youth.